Basic teaching skills of prospective teacher students based on the TBLA (Transcript Based Lesson Analysis) communication pattern at SMP Muhammadiyah 02 Batu - Amira Salsabilla; Sri Wahyuni; Yuni Pantiwati; Eko Susetyarini; Iin Hindun; H. Husamah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Teachers play an important role in transferring or sharing knowledge shared with students. In sharing this knowledge, it is necessary to have a teacher's initial ability in basic teaching skills. Study aimed to obtain an overview of the basic taught skills of prospective Biology Education teacher students at UMM based on the communication pattern of Transcript Based Lesson Analysis. This study used a descriptive approach involving subjects and the Lesson Study team. Data collection obtained from documentation includes video & audio recorder. Data through learning videos and audio were transcribed into writing according to all activities during the learning process. Furthermore, the learning transcripts were analyzed into descriptive data. The results showed that prospective teachers had mastered the nine components of basic teaching skills, namely opening lessons, questioning skills, improving skills, making variations, skills guiding small group discussion skills, small group and individual teaching skills, and class management skills and close the lesson. However, several indicators of the nine components have not been met, such as the skills to ask questions, explain, and guide small group discussions. Thus, this deficiency makes the teacher's activity more dominant than the students which are known through the word count graph of the Transcript Based Lesson Analysis.